Analisis Penyeimbangan Beban Secara Manual Menggunakan Metode Dua Titik Waktu pada Transformator Distribusi 50 kVA PNIAI007 - Rangga Bismantara; Arief Marwanto (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Load imbalance in three-phase distribution transformers can increase neutral current and power losses, thereby reducing the efficiency and reliability of electric power distribution systems. This study aims to analyze the level of load imbalance, power losses caused by neutral current, and the effectiveness of manual load balancing using the two-time-point method, namely peak load time (PLT) and off-peak load time (OPLT). The research was conducted on the PNIAI007 distribution transformer at PT PLN (Persero) ULP Enarotali using a quantitative descriptive approach with a case study design. Data were obtained through measurements of phase currents and neutral current, which were then analyzed to compare conditions before and after load balancing.The results show that the load imbalance level was significantly reduced from more than 29% to 2.47% during daytime operation and 1.21% during nighttime operation. The neutral current decreased from 37.81 A to 14.58 A during the daytime and from 51.76 A to 19.83 A at night. In addition, power losses due to neutral current were reduced by more than 85%. These results indicate that the two-time-point load balancing method is effective in improving the efficiency and operational reliability of distribution transformers.